Vaccine‐related major cutaneous reaction size correlates with cellular‐mediated immune responses after tularaemia immunisation. Issue 1 (19th January 2021) - Salerno‐Gonçalves, Rosangela; Chen, Wilbur H; Mulligan, Mark J; Frey, Sharon E; Stapleton, Jack T; Keitel, Wendy A; Bailey, Jason; Sendra, Eli; Hill, Heather; Johnson, Robert A; Sztein, Marcelo B
Abstract: Objectives: Francisella tularensis, the causative agent of tularaemia, is an exceptionally infectious bacterium, potentially fatal for humans if left untreated and with the potential to be developed as a bioweapon. Both natural infection and live‐attenuated vaccine strain (LVS) confer good protection against tularaemia. LVS vaccination is traditionally administered by scarification, and the formation of a cutaneous reaction or take at the vaccination site is recognised as a clinical correlate of protection. Although previous studies have suggested that high antibody titres following vaccination might serve as a useful surrogate marker, the immunological correlates of protection remain unknown. Methods: We investigated the host T‐cell‐mediated immune (T‐CMI) responses elicited following immunisation with LVS vaccine formulated by the DynPort Vaccine Company (DVC‐LVS) or the United States Army Medical Research Institute of Infectious Diseases (USAMRIID‐LVS). We compared T‐CMI responses prompted by these vaccines and correlated them with take size. Results: We found that both LVS vaccines elicited similar T‐CMI responses. Interestingly, take size associated with the T cells' ability to proliferate, secrete IFN‐γ and mobilise degranulation, suggesting that these responses play an essential role in tularaemia protection. Conclusions: These results renew the appreciation for vaccination through the scarification as a prime route of inoculation to target pathogens driving specific T‐CMI responses and provide further evidence that T‐CMI plays a role in protection from tularaemia. Abstract : The actual immunological correlate(s) of protection from tularaemia in humans remain(s) unknown. As with smallpox, take is widely accepted as a clinical correlate of protection against tularaemia. We report, for the first time, a correlation between take‐lesion size and cellular‐mediated immune responses in humans after tularaemia immunization.